Vicente de la Fuente y Bueno, prototype of historian and nineteenth-century investigator - Ramírez Jerez, Pablo (Revista General de Información y Documentación, 2014)
This paper analyses the character of Vicente de la Fuente y Bueno, theologian, Catholic apologist, University professor and academic, one of the leading of 19th century Spanish historians, and a person with a huge prestige within the academic and university environments of his age. He reached the post of Rector at Madrid Central University and was appointed as a member of two Royal Academies, History and Moral and Political Sciences. He was a deep and serious historian, who dug out hundreds of documents for his various works, searching in all kind of archives. His works deal mainly with history of Aragón and Spanish religious history, albeit he also stood out in another matter, Ecclesiastical law, and as the editor of several historical works.